KUALITAS KOKON ULAT SUTERA (Bombyx mori L.) RAS CINA, RAS JEPANG, DAN JENIS HIBRID DENGAN PAKAN DAUN MURBEI - Deni, .; Diba, Farah; Tavita, Gusti Eva (Universitas Tanjungpura, 2019)
Silk worm cocoon is one of the non timber forest product which potential to develop in West Kalimantan. The aim of the research was to evaluate the best cocoon from silk worm consist of Chinese cocoon, Japanese cocoon and Hybrid cocoon with murbei leaf as a food source. The research was conducted in Silviculture laboratory in Forestry Faculty Tanjungpura University. The silk worm was preparation in laboratory condition until got instar III. When the silk worm got instar IV the sample of each silk worm from each types (Chinese, Japanese and Hybrid) with number 100 silk worm was separated for the evaluate on quality of the cocoon. The data of cocoon quality consist of the weight of fresh cocoon, the survival of silk worm, the amount of consumed the murbei leaf, percentage of cocoon skin and the percentage of fail cocoon. The quality of silk worm cocoon was based on SNI Standard from Balai Persuteraan Alam Indonesia. Result of the research showed that from the three type of silk worm cocoon, the silk worm from Chinese cocoon has the average values of percentage of skin cocoon around 22.1067% (included on Class B), cocoon weight was 0.9023 gram (included on Class D), and the percentage of fail cocoon was 22.50% (included on Class D). Meanwhile on silk worm from Japanese cocoon has the average values of percentage of skin cocoon around 18.9223% (included on Class C), cocoon weight was 1.21567 gram (included on Class C), and the percentage of fail cocoon was 5.4348% (included on Class C). Silk worm from Hybrid cocoon has the average values of percentage of skin cocoon around 22.8624% (included on Class B), cocoon weight was 1.3489 gram (included on Class C), and the percentage of fail cocoon was 4.1667% (included on Class C). The temperature for breeding the silk worm was 27-30 The best cocoon quality was achieved from hybrid types. Keywords: Chinese type, cocoon, Hybrid types, Japanese types, murbei, silkworm